2018
DOI: 10.3947/ic.2018.50.3.210
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella pneumoniaeLiver Abscess

Abstract: Since the mid 1980s, the prevalence of liver abscess caused by hypervirulent Klebsiella pneumoniae strain has increased in Asia, particularly in Taiwan and Korea. This strain is mostly K1 or K2 serotype, and has hypercapsular and hypermucoid phenotypes. Most infections are community acquired, and patients rarely have a hepatobiliary disease prior to infection. Clinical manifestations are characterized by fever and high C-reactive protein, and metastatic infections, such as septic emboli in the lung and endopht… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 44 publications
3
84
0
2
Order By: Relevance
“…It is an aetiological agent of septicaemia, pneumonia, soft tissue infections, urinary tract infections, surgical site infections and catheter-related infections (Podschun and Ullmann, 1998;Abbot, 2003). This pathogen can also cause community-acquired infections, and over the past three decades, K. pneumoniae has become a major cause of pyogenic liver abscess, complicated with metastatic meningitis and endophthalmitis, and this emerging disease has been reported worldwide (Ko et al, 2002;Ohmori et al, 2002;Okano et al, 2002;Chung et al, 2008;Tsai et al, 2008;Jun, 2018;Wang et al, 2018). Another study demonstrated the important role of K. pneumoniae in bacteraemic community-acquired pneumonia (CAP), as this pathogen accounted for more than half of CAP cases in Taiwan (49/95, 51.5%) during 2001(Lin et al, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…It is an aetiological agent of septicaemia, pneumonia, soft tissue infections, urinary tract infections, surgical site infections and catheter-related infections (Podschun and Ullmann, 1998;Abbot, 2003). This pathogen can also cause community-acquired infections, and over the past three decades, K. pneumoniae has become a major cause of pyogenic liver abscess, complicated with metastatic meningitis and endophthalmitis, and this emerging disease has been reported worldwide (Ko et al, 2002;Ohmori et al, 2002;Okano et al, 2002;Chung et al, 2008;Tsai et al, 2008;Jun, 2018;Wang et al, 2018). Another study demonstrated the important role of K. pneumoniae in bacteraemic community-acquired pneumonia (CAP), as this pathogen accounted for more than half of CAP cases in Taiwan (49/95, 51.5%) during 2001(Lin et al, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…HA is invaded by microbes via bile ducts, blood stream (hepatic artery and portal vein) or by contiguous spread [11,12] and PLA is accused of the majority causes of HA [1] . Numerous studies show the risk factors which predispose patients to PLA, including immune-compromised state (immunodeficiency, chemotherapy and etc.…”
Section: Discussionmentioning
confidence: 99%
“…The recent improvement in public health in Korea has resulted in reducing the prevalence of amebic liver abscess, whereas PLA accounts for 73%-96% of liver abscesses, with KP being the primary causative pathogen [8]. In particular, immunocompromised patients with KP-PLA and conditions such as DM or cancer are at a risk of severe complications, including bacteremia, septic shock, and multiple organ failure [8].…”
Section: A B C Dmentioning
confidence: 99%